2017
DOI: 10.1007/s41650-017-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

On the security of warning message dissemination in vehicular Ad hoc networks

Abstract: Abstract-Information security is an important issue in vehicular networks as the accuracy and integrity of information is a prerequisite to satisfactory performance of almost all vehicular network applications. In this paper, we study the information security of a vehicular ad hoc network whose message may be tampered by malicious vehicles. An analytical framework is developed to analyze the process of message dissemination in a vehicular network with malicious vehicles randomly distributed in the network. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Because propagation speed of message is much faster than moving speed of vehicle, it ignores the time it takes to propagate messages from a vehicle to other vehicles. e process is considered to be a static network [22]. erefore, when a vehicle receives a message, it can be assumed that the message is at the current moment.…”
Section: Network Model and Data Propagation Modelmentioning
confidence: 99%
“…Because propagation speed of message is much faster than moving speed of vehicle, it ignores the time it takes to propagate messages from a vehicle to other vehicles. e process is considered to be a static network [22]. erefore, when a vehicle receives a message, it can be assumed that the message is at the current moment.…”
Section: Network Model and Data Propagation Modelmentioning
confidence: 99%
“…Hence, cooperation will also need to be robust against malicious coalition behaviours. The work in [71] which showed that the probability of correct message delivery reduces to its minimum after the proportion of malicious vehicles in the network crosses a threshold, that is, trust requires a collective effort.…”
Section: B Trusted Communications and Deception-proofingmentioning
confidence: 99%
“…With these limitations in mind, it is highly demanded to achieve highly efficient anti-jamming results for future wireless communications. How to guarantee the reliability of wireless communications still is an open challenge [11], [12].…”
mentioning
confidence: 99%